Fiṭrah in Islam and Ren Xing in Confucianism: their relation to Islamic and Confucian ethics - Mohd Nor, Nur Suriya (2018)
This paper discusses the concept of human nature in Islam and in Confucianism. The researcher makes a comparison between the concept of fiṭrah in Islam and its relation to Islamic Ethics or ―good character‖, and the concept of ren xing or ―inherently good‖ of Confucianism. In order to explore both concepts vis-à-vis the human nature, the researcher employs textual analysis and comparative methodology on written materials related to the topic. The findings reveal several similarities between the two concepts – fiṭrah and ren xing – as both deal with human nature, which includes human characters and behaviours, the merits of good and the vile of evil, and the idea of mind and soul, among others.